Efficient resolution of 3-aryloxy-1, 2-propanediols using CLEA-YCJ01 with high enantioselectivity. Issue 24 (3rd May 2019) - Wang, Bin; Wu, Bin; He, Bingfang
Abstract : CLEAs-YCJ01 had high enantioselectivity to a series of 3-aryloxy-1, 2-propanediols with high conversion (≥49.3%), favorable ee values (94.8–99.5%) for S -diacetates and high ee values (92.1–99.2%) for R -monoacetate. Abstract : The lipase YCJ01 from Burkholderia ambifaria is an organic solvent-stable enzyme and its activity can be activated by a hydrophobic solvent due to the "interface activation" mechanism. The activity of lipase YCJ01 increased by 2.1-fold with t -butanol as the precipitant even after cross-linking. The cross-linked enzyme aggregates of lipase YCJ01 (CLEAs-YCJ01) were found to be efficient for resolving 3-(4-methylphenoxy)-1, 2-propanediol (MPPD) through sequential esterification. Excellent enantioselectivity towards MPPD ( E > 400), excellent enantiomeric excess (ee) values of 99.2% for S -diacetates and 99.1% for R -monoacetate, and high yield (49.9%) were achieved using a high substrate concentration (180 mmol L −1 ). Thus, R - and S -type compounds with excellent ee values were simultaneously obtained, and MPPD was resolved by CLEAs-YCJ01. CLEAs-YCJ01 also showed high operational stability and maintained 91.2% residual activity after ten batches. To further evaluate the substrate specificity of CLEAs-YCJ01, a series of 3-aryloxy-1, 2-propanediols (six analogues of MPPD) was applied as substrates for resolution. Under the optimized reaction conditions of reaction temperature of 35 °C, MPPD concentration of 180 mmol L −1, molar ratio of vinyl acetate to MPPD of 3 : 1, and isopropyl ether as the solvent, CLEAs-YCJ01 exhibited relatively strict enantioselectivity towards all the analogues of MPPD with a high yield (≥49.3%), favourable ee values (94.8–99.4%) for S -diacetates, and high ee values (92.1–99.2%) for R -monoacetate, which shows potential prospects for industrial applications.